EVALUATION OF MICRO LEAKAGE OF ROOT CANALS FILLED WITH DIFFERENT OBTURATION TECHNIQUES: AN IN VITRO STUDY - Lone, Maham Muneeb; Khan, Farhan Raza (Journal of Ayub Medical College Abbottabad, 2018)
Background: Despite a plethora of studies done comparing different obturation techniques using gutta-percha, there is no consensus as to which obturation technique results in a ’˜better’ sealing of root canal space. Aims of the study are to compare mean apical micro leakage in root canals of extracted teeth obturated with cold laterally compacted gutta-percha and thermoplasticised injectable gutta-percha using calcium hydroxide based sealer. Methods: It was an in-vitro experimental study carried out using extracted teeth. After access cavity preparation and canal preparation in 70 teeth, they were randomly divided into 2 groups and filled with two different obturation techniques using Sealapex sealer. Teeth were placed in 2.0% methylene blue solution, sectioned longitudinally, observed under microscope and images were captured using microscope attached camera. Amount of dye penetration was measured in millimetre from apex to most coronal part of dye penetration. Data was analysed using SPSS 20.0. Mean and standard deviation of continuous variables was computed. Independent Sample t- test was applied to compare micro leakage values in the two study groups. Level of significance was kept at 0.05. Results: According to the measurements, obturation with Obtura-II and Sealapex was leakier than the other group, with a mean dye penetration of 1.91±1.15mm. There was a statistically significant difference in dye penetration among the two groups. Conclusions: Cold lateral compaction plus Sealapex was the best combination for obturation as it exhibited least microleakage. Obtura II-Sealapex combination should be used with caution as it showed maximum microleakage. For obturation of single rooted teeth, we recommend cold lateral condensation with Sealapex sealer as it showed better sealability. Obtura-II and Sealapex should be used with caution in single rooted teeth as this group showed the maximum leakage. Keywords: Dye penetration; Endodontics; Obturation